Existe-t-il une gouvernance des systèmes d’innovation en Afrique du Nord et au Moyen-Orient? - Rigas Arvanitis; Hatem M’henni; Lena Tsipouri (Maghreb - Machrek, 2010)
Is there an Innovation Systems Governance in North Africa and in the Middle East? This article summarizes observations on the technological and innovation level of four Mediterranean countries (Egypt, Jordan, Morocco, Tunisia). Although these concepts are still controversial, we try to examine the specific issue of the governance of innovation policies. This approach is most adapted to countries where the “national system of innovation” concept seems not to apply. Our findings show that even though a real political will has been raised on innovation by the governments, the difficulties remain on many key aspects: (1) State Maghreb-Machrek, N˚ 202, Hiver 2009-2010 policies have served mainly to increase public research and the recent efforts to define the contours of an innovation policy have had little if no impact on the economy; (2) we suggest this is due to the fact that State policies oriented to promote innovation are badly accepted by other economic actors (due to a “top-down” approach that prevails in all four countries); (3) innovation policies seem hesitant and discontinuous and the voluntarism is rather of circumstances (changes in Tunisia, in Morocco, in Jordan, in Egypt); (4) scientific research is real in these countries and is based on individuals’ efforts, and innovation is developing in enterprises that have little knowledge of policies that are supposed to be oriented to tem. We conclude that the “world of innovation” is growing, even when the State seems to play a predominant role it has little impact and a low efficiency.